Practices of financial income accounting in budget organizations - N. Abdullayeva (International Journal on Orange Technologies, 2021)
This article describes the fixed assets recognition in budget organizations and their practical aspects. There are practical recommendations for the recognition and accounting of fixed assets in budget organizations